Mesenchymal stem cells derived extracellular vesicles for chronic kidney disease: pleiotropic mechanisms of actions of a versatile therapy - Ceccotti, Elena; Quaglia, Marco; Camussi, Giovanni; Bruno, Stefania (Frontiers in Bioengineering and Biotechnology, 2025)
Chronic kidney disease (CKD) has increasingly become a major health concern worldwide, globally affecting 10%–15% of adults, with significant implications for morbidity and mortality. This progressive condition can potentially evolve into end-stage renal disease (ESRD), requiring dialysis or renal transplant. However, the heaviest impact of CKD is due to an associated increased cardiovascular risk, due to frequently coexisting hypertension and diabetes and non-traditional risk factors, including accumulation of atherogenic toxins, alteration of calcium-phosphate balance, oxidative stress and chronic microinflammation. Mesenchymal stem cells (MSCs) have been proposed as a therapy for CKD due to their immunomodulating and tissue repairing properties. It has been proposed that extracellular vesicles (EVs) may mediate the therapeutic effects of the cells of origin and MSC-EVs have shown promise as treatment of different aspects of CKD in experimental settings. Their anti-fibrotic and anti-apoptotic properties may inhibit progression of CKD and promote healing of tubular and glomerular damage. MSC-EVs can prevent epithelial-mesenchymal transition, a key mechanism of evolution of acute kidney injury towards CKD. These actions may inhibit development of interstitial fibrosis and accumulation of the extracellular matrix components (ECM), key lesions which promote the progression of CKD. Furthermore, MSC-EVs also exert anti-inflammatory and anti-oxidant properties which may reduce vascular damage and cardiovascular risk associated with CKD. For example, Human Liver Stem Cell (HLSC)-derived EVs (HLSC-EVs) can reverse renal and cardiac alterations. As shown in a murine model of partial nephrectomy, HLSC-EVs shuttled proteases with ECM remodeling activity, lending support to the possibility of a simultaneous cardio-nephroprotective effect. Adipose, umbilical cord and inducible- MSCs are other possible sources of EVs potentially applicable to obtain reparative processes in CKD and ESRD. Overall, building experimental evidence suggests that MSC-EVs derived from different sources are a promising therapeutic tool to prevent development and progression of CKD and to reduce related cardiovascular risk. The strength of this therapy lies in its multi-level and pleiotropic actions which appear to interfere with many key etiopathogenetic mechanisms of CKD. Interesting future perspective is a combined therapy associating MSC-EVs with drugs to achieve synergistic effects and recent finding indicate the feasibility of this approach.